Inoculation with remnant prairie soils increased the growth of three native prairie legumes but not necessarily their associations with beneficial soil microbes. (23rd February 2020) - Grman, Emily; Allen, Jamie; Galloway, Emily; McBride, Justin; Bauer, Jonathan T.; Price, Paul A.
Abstract : Restoring the diversity of plant species found in remnant communities is a challenge for restoration practitioners, in part because many reintroduced plant species fail to establish in restored sites. Legumes establish particularly poorly, perhaps because they depend on two guilds of soil microbial mutualists, rhizobial bacteria and arbuscular mycorrhizal (AM) fungi, that may be absent from restored sites. We tested the effect of soil microorganisms from remnant and restored prairies on legume growth by inoculating seedlings of Lespedeza capitata, Amorpha canescens, and Dalea purpurea with soil from 10 restored prairies and 6 remnant (untilled) prairies from southwest Michigan. We generally found support for the hypothesis that restored prairie soils lack microbes that enhance prairie plant growth, although there was variation across species and mutualist guilds. All three legumes grew larger and two legumes ( Lespedeza and Amorpha ) produced more nodules when inoculated with soil from remnant prairies, suggesting that low quantity and/or quality of rhizobial partners may limit the establishment of those species in restored prairies. In contrast, no legume experienced greater root colonization by AM fungi in remnant prairie soils, suggesting equivalent quantity (but not necessarily quality) of fungal partners in remnant and restored prairie soils. We detected no evidence of spontaneous recovery of the community of beneficial soil microbes in restorations. These results suggest that the absence of rhizobia, a largely overlooked component of prairie soils, could play a strong role in limiting restored prairie diversity by hindering legume establishment. Active reintroduction of appropriate rhizobial strains could enhance prairie restoration outcomes.